A Comparative Study of Speech Levels in Kelanjuh Lauq Central Lombok and Kelayu East Lombok - Husnawati Husnawati (IJECA (International Journal of Education and Curriculum Application), 2018)
Politeness which is reflected in behavior and speech has different standards in every place as a form of cultural treasures. This is motivated by various things, not only social stratification in society and nobility, but also age, education, familiarity, and speech situation. The community members of Kelanjuh Lauq Central Lombok use Sasak "subtle" language not only to show their social status and nobility, but also to maintain Sasak subtle language and to acquire language for children. In contrast, in Kelayu East Lombok, the standard of decency in speech does not reflect one's nobility, but rather the social status and the level of religious understanding. The use of subtle language is important that everyone can put him or herself correctly and proportionally to maintain social harmony in a community.